Influence of Marine Fish Amino Extractson Growth, Yield and Quality of Curly leaf Kale - Hoktha, Pimchana; Benchasri, Sorapong (Journal of Advanced Development in Engineering and Science, 2024)
The objective of this research was to compare the Influence of growth, yield and yield components of kale after receiving marine fish amino acid (MFA) at Thaksin University from January to August 2023. MFAs were sprayed as a foliar spray on curly leaf kale in the second weeks. Spraying will be done twice a week. MFAs were sprayed 5 concentrations consisting of 0.00, 1.50, 3.00, 4.50 and 6.00 ml/l. In this experiment, 0.00 ml/l was determined as a control treatment. The experiment was planned in a Completely Randomized Design with 4 replications. The results showed that the height, leaf width, leaf length, canopy width, stem diameter, and stem lengthwere statistically different in each treatments.The MFA 3.00 ml/l showed the highest of plant height and stem length, which were 43.02 and 17.21 cm/plant, respectively, while the concentration level was 1.50 ml/l showed the average of leaf width, leaf length, canopy width, and stem length, averaged 17.50 cm/leaf, 36.75 cm/leaf, 62.11 cm/plant and 3.79 cm/plant, respectively. In addition, the concentration level was 3.00 ml/l showed the average leaf weightand number of leaves/plant higher than other concentration levels, with an average of 12.66 grams/leaf and 25.33 leaves/plant, respectivelyandthe highest average leaf weight/ plant was 320.68 grams/plant, but not statistically different from the concentration levels 1.50, 4.50, and 6.00 ml/l gave averages of 306.76, 298.18 and 273.79 grams/plant, respectively, while being statistically different from the concentration level of 0.00 ml/l showed the lowest leaf weight about 210.61 grams/plant.